Bistatic Radar - Willis, Nicholas J. 1934- (SciTech Publishing Inc, 2005)
This book is dedicated on bistatic radar. It summarizes and codifies subsequent bistatic radar research and development. It discusses static radar research and development, defines and resolves many issues and controversies plagung bistatic radar, including predicted performance, monosatic equivalence, bistatic radar cross section and resolution, bistatic Doppler, hitchiking, SAR, ECM/ECCM, and, most importantly, the utility of bistatic radars
Keywords: Doppler radar; Electronic countermeasures; Radar; Radar cross sections; Synthetic aperture radar